3D Numerical simulation of turbulent heat transfer and Fe3O4/nanofluid annular flow in sudden enlargement - Togun Hussein (EDP Sciences, 2021)
In this paper, 3D Simulation of turbulent Fe3O4/Nanofluid annular flow and heat transfer in sudden expansion are presented. k-ε turbulence standard model and FVM are applied with Reynolds number different from 20000 to 50000, enlargement ratio (ER) varied 1.25, 1.67, and 2, , and volume concentration of Fe3O4/Nanofluid ranging from 0 to 2% at constant heat flux of 4000 W/m2. The main significant effect on surface Nusselt number found by increases in volume concentration of Fe3O4/Nanofluid for all cases because of nanoparticles heat transport in normal fluid as produced increases in convection heat transfer. Also the results showed that suddenly increment in Nusselt number happened after the abrupt enlargement and reach to maximum value then reduction to the exit passage flow due to recirculation flow as created. Moreover the size of recirculation region enlarged with the rise in enlargement ratio and Reynolds number. Increase of volume Fe3O4/nanofluid enhances the Nusselt number due to nanoparticles heat transport in base fluid which raises the convection heat transfer. Increase of Reynolds number was observed with increased Nusselt number and maximum thermal performance was found with enlargement ratio of (ER=2) and 2% of volume concentration of Fe3O4/nanofluid. Further increases in Reynolds number and enlargement ratio found lead to reductions in static pressure.